2020
DOI: 10.34118/jbms.v7i1.707
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of autoclaved aerated concrete (AAC) blocks with reference to its potential and sustainability

Abstract: The traditional bricks are the main building materials that are used extensively in the construction and building industry. Autoclaved Aerated Concrete blocks are recently one of the newly adopted building materials. The Autoclaved aerated concrete (AAC) is a product of fly ash which is mixed with lime, cement, and water and an aerating agent. The AAC is mainly produced as cuboid blocks and prefabricated panels. The Autoclaved aerated concrete is a type of concrete that is manufactured to contain lots of close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…According to the literature, AAC is one of the confirmed green structures that permits the use of many raw material types in its manufacture. Some of these substitute materials are effective in reducing cement consumption in the production of AAC, thus leading to a reduction in greenhouse gases [76,77]. The characterization of QWF and ESP, in this study, revealed that these waste materials contain the key components for tobermorite synthesis such as SiO 2 and CaO.…”
Section: Discussionmentioning
confidence: 70%
“…According to the literature, AAC is one of the confirmed green structures that permits the use of many raw material types in its manufacture. Some of these substitute materials are effective in reducing cement consumption in the production of AAC, thus leading to a reduction in greenhouse gases [76,77]. The characterization of QWF and ESP, in this study, revealed that these waste materials contain the key components for tobermorite synthesis such as SiO 2 and CaO.…”
Section: Discussionmentioning
confidence: 70%
“…However, the clay brick is produced by drying and firing clay or shale raw material, forming a sintered porous structure [55], [56], [57]. Also, the AAC contains cement, but it is lightweight to mitigate the harmful environmental impacts [13] Turning to the three last scenarios, when adding the XPS to the three wall types, the environmental impacts have been increased by 1.24 𝑝𝑡, 1.86 𝑝𝑡, and 2.55 𝑝𝑡, that is, an incremental rate of 13%. The highest value among all scenarios is the sixth one, which is (4 𝑐𝑚 XPS + 20 𝑐𝑚 cement brick) composition.…”
Section: Single Score Resultsmentioning
confidence: 99%
“…Regarding the LCA of AAC and various wall materials, Kamal [13] has examined AAC blocks, emphasizing their sustainability and potential. The advantages of AAC blocks for the environment, including lower energy use and greenhouse gas emissions during production and use, have also been covered in the article.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though FAB is the per-cost price and is the cheapest among the bricks considering the number of bricks, the number of bricks is more compared to others, which does not give any economic benefits when the whole construction is considered. AACB are proven green structural material that may be used for commercial, contemporary, and private projects [41]. AACB's per piece cost is higher than other bricks.…”
Section: Description Of Life-cycle Assessment (Lca) Inputs Correspond...mentioning
confidence: 99%